The Pedagogy of the Online Wisdom Community: Forming Church Ministers in a Digital Age - Esselman, Thomas (Teaching theology and religion, 2004)
While electronic learning is transforming the face of higher education today, some in the theological community question whether it is appropriate for the specific goals of graduate level theological formation for ministry. Drawing on the work of one theological faculty, this article answers yes. The author describes the school's hybrid model of distance education pedagogy. He discusses the underlying teaching and learning principles that guided the faculty in their development of this model, and, in particular, the pedagogical ideal of the learning cohort as a “wisdom community.” Web-based instruction can be effectively designed to nurture wisdom communities for integrative learning. The author describes the “pedagogy of the online wisdom community” from his experience of Web-based distance education teaching. The growing demand for ministry formation programs, particularly in mission areas, underlines the urgent need for continued study of the role of technology in theological pedagogy.